A qualitative study of persons with persistent postconcussion symptoms and clinicians with concussion expertise to inform the development of a concussion-specific questionnaire. Issue 23 (6th November 2021) - van Ierssel, Jacquie; O'Neil, Jennifer; Sveistrup, Heidi; Marshall, Shawn; Graham, Ian
Abstract: Purpose: To explore the experiences of adults with persistent postconcussion symptoms and clinicians to inform the development of a concussion-specific questionnaire. Methods: Using a qualitative descriptive design, we conducted 10 focus groups with persons with persistent post-concussion symptoms ( n  = 35; female 66%; age range 19.0–65.1 years) and semi-structured interviews with clinicians with concussion expertise ( n  = 16; female 81%). Thematic analysis was used to identify themes within their narratives. The International Classification of Functioning, Disability and Health (ICF) provided a standardized language for coding. Results: Three overarching themes emerged from the data: Functioning, Environmental and Personal Factors, and Capacity . Functioning mapped closely onto Activities and Participation within the ICF. Contextual factors, both Environmental and Personal, had a significant influence on functioning following concussion. Capacity was a unique finding that described how long a person is able to engage in a task before the onset or worsening of symptoms. Conclusions: Capacity is fundamental to measuring limitations in functioning based on symptom threshold and time to recovery. The impact of contextual factors on functioning needs to be considered on a continuum from barrier to facilitator. These findings provide the basis for the development of a concussion-specific questionnaire. Implications for Rehabilitation: Clinicians should explore with their patients limitations across all areas of functioning. Clinicians should explore and address support and relationships, attitudes of others, access to affordable and high-quality healthcare, coping strategies, and a patient's own knowledge of concussion as these influence functioning. Current guidelines recommend a symptom-based approach to concussion management, whereas persons with concussion emphasize the importance of measuring functional capacity. Capacity is defined as the length of time one can perform a task before symptom onset, primarily fatigue. Currently, no concussion-specific measure of functioning exists.